2023
DOI: 10.1161/cir.0000000000001168
|View full text |Cite|
|
Sign up to set email alerts
|

2023 AHA/ACC/ACCP/ASPC/NLA/PCNA Guideline for the Management of Patients With Chronic Coronary Disease: A Report of the American Heart Association/American College of Cardiology Joint Committee on Clinical Practice Guidelines

Salim S. Virani,
L. Kristin Newby,
Suzanne V. Arnold
et al.

Abstract: AIM The “2023 AHA/ACC/ACCP/ASPC/NLA/PCNA Guideline for the Management of Patients With Chronic Coronary Disease” provides an update to and consolidates new evidence since the “2012 ACCF/AHA/ACP/AATS/PCNA/SCAI/STS Guideline for the Diagnosis and Management of Patients With Stable Ischemic Heart Disease” and the corresponding “2014 ACC/AHA/AATS/PCNA/SCAI/STS Focused Update of the Guideline for the Diagnosis and Management of Patients With Stable Ischemic Heart Disease.” … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
161
0
12

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 396 publications
(173 citation statements)
references
References 1,186 publications
(1,505 reference statements)
0
161
0
12
Order By: Relevance
“…Chronic Coronary Disease Guidelines Sunil V. Rao , MD; Harmony R. Reynolds , MD; Judith S. Hochman , MD C hronic coronary disease (CCD) affects millions of people worldwide and is responsible for significant morbidity, mortality, and costs. CCD as defined in the 2023 guideline 1 includes patients who may or may not have classic signs and symptoms of coronary artery disease. The 2023 guideline reflects this heterogeneity by including patients stabilized after acute coronary syndrome hospitalization; those with ischemic cardiomyopathy, stable angina or equivalent with or without a positive imaging test; vasospasm or microvascular disease; and positive noninvasive screening test leading to a clinician diagnosis of coronary artery disease .…”
Section: Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Chronic Coronary Disease Guidelines Sunil V. Rao , MD; Harmony R. Reynolds , MD; Judith S. Hochman , MD C hronic coronary disease (CCD) affects millions of people worldwide and is responsible for significant morbidity, mortality, and costs. CCD as defined in the 2023 guideline 1 includes patients who may or may not have classic signs and symptoms of coronary artery disease. The 2023 guideline reflects this heterogeneity by including patients stabilized after acute coronary syndrome hospitalization; those with ischemic cardiomyopathy, stable angina or equivalent with or without a positive imaging test; vasospasm or microvascular disease; and positive noninvasive screening test leading to a clinician diagnosis of coronary artery disease .…”
Section: Perspectivementioning
confidence: 99%
“…Three class 3 recommendations in the CCD guidelines, pertaining to routine testing in patients who do not have a change in clinical or functional status, are notable: (1) no benefit of routine periodic testing with coronary computed tomography angiography or stress testing; (2) no benefit of periodic assessment of LVEF; and (3) harm for routine coronary angiography in this setting. Randomized and observational studies have shown no benefit of routine testing follow-up for ischemia, anatomical progression of coronary artery disease, or LV function in stable patients with CCD.…”
Section: Recommendation Against Routine Anatomic or Ischemic Testing ...mentioning
confidence: 99%
“…4 Notably, this possible ancillary role of ExECG is also echoed in American guidelines for patients with chronic coronary syndromes. 67 Some hindrances should be acknowledged when considering the use of ExECG in the assessment of suspected CAD. 16,57,63,68,69 First, technical issues such as ECG quality or baseline abnormalities (including left bundle branch block or ventricular pacing, both of which could affect interpretation) should be considered.…”
Section: Ihdmentioning
confidence: 99%
“…Another diagnostic limitation in clinical practice is the ineffective allocation and poor use of medical resources. CHD diagnosis depends predominantly on coronary CT angiography (CTA) or angiography alone . However, a subset of patients who presented with chest pain symptoms and underwent pertinent tests exhibited no coronary artery abnormalities .…”
Section: Introductionmentioning
confidence: 99%